Frankenstein: ethics and law trapped in aesthetics - Cardinaux, Nancy (2021)
This article aims to question some relations between ethics and law concerning the aesthetics omnipresent in the text before two hundred years after the publication of a Frankenstein text that is part of our social imaginary. The reading of Frankenstein’s stories can illuminate, both the creator and the created monster, the ethics of scientific knowledge, the denial or invisibilization of otherness, the treatment of inequalities, and the ethical foundation of human rights.